PROBABLE NURSERY GROUND OF SILVERPOMFRET PAMPUS ARGENTEUS (EUPHER) OFF NAWABUNDER (GUJARAT) - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
Large quantities of small-sized silverpomfret, Pampus argenteus (Eupher),mostly in the size range of 20-99 mm, were caught in dol net at Nawabunder overa number of months m 1979-80 and 1980-81 Ashing seasons. The estimatedcatch being 50.7 and 40.7 tonnes, respectively , the inshore area off Nawabunderseems to form an important nursery ground for silverpomfret. The need for appropriateregulatory measures on fktl-net fishing in these grounds, therefore, is indicated.